Positive electrode material for lithium ion battery, positive electrode for lithium ion battery, and lithium ion battery
Patent Information
- Application Number
- CN202111153053.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-30
- Filing Date
- 2021-09-29
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2041-09-29
AI Technical Summary
[0025]根据本发明,可提供一种能够得到可提高低温下的输出特性的锂离子电池的锂离子电池用正极材料、使用了该锂离子电池用正极材料的锂离子电池用正极、及具备该锂离子电池用正极的锂离子电池。
Smart Images

Figure BDA0003287814780000181 
Figure HDA0003287814790000011
Abstract
Description
Technical Field
[0001] This invention relates to a positive electrode material for lithium-ion batteries, a positive electrode for lithium-ion batteries, and a lithium-ion battery. Background Technology
[0002] The battery possesses a variety of desirable characteristics, and its improvement is being studied.
[0003] For example, in Patent Document 1, in order to suppress the peeling of the carbonaceous coating on the surface of the primary particles of the positive electrode active material and to improve the positive electrode density while ensuring electronic conductivity, a positive electrode material for lithium-ion secondary batteries is disclosed. This material comprises active material particles containing a central particle represented by a specified chemical composition and an active material particle covering the surface of the central particle. The coarse particle ratio of the particle size distribution is 35% or more and 65% or less, and the median particle size of the active material particles is 0.50 μm or more and 0.80 μm or less.
[0004] Furthermore, for example, in Patent Document 2, in order to suppress the degradation of electrode durability caused by the dissolution of metal from the positive electrode material and to obtain a lithium-ion secondary battery that balances high input / output characteristics and good cycle characteristics, a positive electrode material for a lithium-ion secondary battery is disclosed. This material comprises aggregated particles formed by the aggregation of primary particles of a positive electrode active material with a predetermined chemical composition coated with a carbonaceous film. The positive electrode active material has a carbon content of 0.0084 wt% / nm or more and 0.0358 wt% / nm or less per microcrystal. The peak intensity ratio (Ig) of the D band and G band of the Raman spectrum obtained by Raman spectroscopy is... D / I G The cumulative particle size distribution is 10% or higher and 1.15 or lower, with the cumulative percentage of particle size (D10) being 1 μm or higher and 5 μm or lower, and the cumulative percentage of particle size (D90) being 90% or lower than 15 μm.
[0005] Furthermore, for example, in Patent Document 3, in order to obtain an electrode material capable of suppressing voltage drop during high-speed discharge at low temperatures, an electrode material is disclosed, which is a particle-shaped electrode material formed by forming a carbonaceous coating on the surface of electrode active material particles having an olivine-type crystal structure. The average ratio of the discharge capacity of a single particle of the electrode material at -10°C to the discharge capacity of a single particle at -10°C is 0.50 or more, and the XRD (CuKα ray source) peak of the (002) plane caused by the graphene layer of the carbonaceous coating is 2θ = 25.7° or less.
[0006] Patent Document 1: Japanese Patent No. 6288338
[0007] Patent Document 2: Japanese Patent No. 6627932
[0008] Patent Document 3: Japanese Patent No. 5743011 Summary of the Invention
[0009] The problem the invention aims to solve
[0010] One of the desirable characteristics of a battery is its output performance at low temperatures. However, in lithium iron phosphate coated on carbon, lithium ions are inserted and extracted through the gaps between the carbon atoms. Therefore, if the lithium iron phosphate is coated with carbon, which allows for easy electron migration, lithium ions will have difficulty passing through the gaps between the carbon atoms, resulting in a decrease in low-temperature performance.
[0011] The carbon coating used in the cathode materials described in Patent Documents 1 and 2 is graphene-like carbon, therefore its low-temperature performance is not excellent. Furthermore, although the carbon coating used in the electrode material described in Patent Document 3 is graphene-like, it is an irregular carbon coating, leaving room for further research.
[0012] The present invention was made in view of this situation, and its object is to provide a positive electrode material for a lithium-ion battery that can improve the output characteristics of a lithium-ion battery at low temperatures, a positive electrode for a lithium-ion battery using the positive electrode material, and a lithium-ion battery having the positive electrode.
[0013] Solution for solving the problem
[0014] <1> A positive electrode material for lithium-ion batteries, comprising primary particles or aggregates thereof coated with a carbonaceous film, having a powder resistivity of 500 Ω·cm or higher and 50,000 Ω·cm or lower, and a carbonaceous film mass of 0.7 mg / m³ per unit specific surface area. 2 Above and 1.1 mg / m 2 The following conditions must be met, and the following equation (1) must be satisfied.
[0015] Y≥4.91×10 6 ×e -9.021X (1)
[0016] Y: The resistance of the powder (Ω·cm)
[0017] X: Mass of the carbonaceous coating per unit specific surface area (mg / m²) 2 )
[0018] <2> According to the positive electrode material for lithium-ion batteries described in <1>, wherein,
[0019] The main component of the carbonaceous coating is hard carbon.
[0020] <3> The positive electrode material for lithium-ion batteries according to <1> or <2>, wherein,
[0021] The thickness of the carbon coating is greater than 0.5 nm and less than 10 nm.
[0022] <4> A positive electrode for a lithium-ion battery, which uses any one of <1> to <3> lithium-ion battery positive electrode materials.
[0023] <5> A lithium-ion battery having the positive electrode for a lithium-ion battery described in <4>.
[0024] The effects of the invention
[0025] According to the present invention, a positive electrode material for a lithium-ion battery that can produce a lithium-ion battery with improved output characteristics at low temperatures, a positive electrode for a lithium-ion battery using the positive electrode material, and a lithium-ion battery having the positive electrode are provided. Attached Figure Description
[0026] Figure 1 This is a graph showing the powder resistance relative to the carbon content per unit specific surface area in the cathode materials of Examples 1 to 7, Comparative Examples 1 to 5, and Examples where the manufacturing methods, such as carbon content and calcination atmosphere, were changed. Detailed Implementation
[0027] [Positive electrode material for lithium-ion batteries]
[0028] The positive electrode material for lithium-ion batteries in this embodiment is as follows: it is composed of primary particles or aggregates thereof coated with a carbonaceous film, with a powder resistivity of 500 Ω·cm or more and 50,000 Ω·cm or less, and the mass of the carbonaceous film per unit specific surface area is 0.7 mg / m³. 2 Above and 1.1 mg / m 2 The following conditions must be met, and the following equation (1) must be satisfied.
[0029] Y≥4.91×10 6 ×e -9.021X (1)
[0030] Y: Powder resistance (Ω·cm)
[0031] X: Mass of carbonaceous coating per unit specific surface area (mg / m²) 2 )
[0032] Hereinafter, the cathode material used in lithium-ion batteries will sometimes be referred to simply as "cathode material".
[0033] The positive electrode material for the lithium-ion battery in this embodiment is in the form of electrode active material particles coated with a carbonaceous film. The electrode active material particles are composed of primary particles and secondary particles that are aggregates of the primary particles. Hereinafter, the electrode active material coated with the carbonaceous film will sometimes be referred to as carbonaceous coated electrode active material.
[0034] The detailed method for manufacturing carbon-coated electrode active materials will be described later. Electrode active materials are typically directly carbonized by a carbon source attached to the surface of the electrode active material particles, thereby being coated with a carbon film resembling a layered graphene structure. In this invention, by adjusting the coating method of the carbon source, the atmosphere during calcination of the carbon source, and the calcination time, a specified porous carbon-coated electrode active material can be obtained. Analysis of this carbon-coated electrode active material from the viewpoint of powder resistivity and the mass of the carbon film per unit specific surface area shows that by adopting the structure described in this invention, the output characteristics of lithium-ion batteries at low temperatures (e.g., -30°C) can be improved.
[0035] [Powder resistance]
[0036] In the positive electrode material for lithium-ion batteries of this embodiment, the powder resistivity is 500 Ω·cm or more and 50000 Ω·cm or less.
[0037] If the resistivity of the powder is less than 500 Ω·cm, the carbon structure may become graphitic, the pores for lithium-ion insertion and extraction become smaller, and the capacity at low temperatures decreases. Furthermore, if it exceeds 50,000 Ω·cm, the electronic conductivity of the active material surface cannot be maintained.
[0038] The powder resistivity is preferably 700 Ω·cm or more and 48000 Ω·cm or less, more preferably 800 Ω·cm or more and 46000 Ω·cm or less, and even more preferably 900 Ω·cm or more and 44000 Ω·cm or less.
[0039] The resistivity of the powder can be measured by forming a sample of the positive electrode material under a pressure of 50 MPa, specifically by the method described in the examples.
[0040] [Mass of carbonaceous coating per unit specific surface area]
[0041] In the positive electrode material for lithium-ion batteries of this embodiment, the mass of the carbonaceous coating per unit specific surface area is 0.7 mg / m³. 2 Above and 1.1 mg / m 2 the following.
[0042] If the mass of the carbonaceous coating per unit specific surface area is less than 0.7 mg / m² 2 It can maintain electronic conductivity, and if it exceeds 1.1 mg / m2 This will become a barrier to lithium ion insertion / extraction, resulting in reduced performance at low temperatures.
[0043] The preferred mass of the carbonaceous coating per unit specific surface area is 0.705 mg / m³. 2 Above and 1.095 mg / m 2 The following is more preferably 0.71 mg / m³ 2 Above and 1.09 mg / m 2 The following is a further preferred value: 0.71 mg / m³ 2 Above and 1.08 mg / m 2 the following.
[0044] The mass of the carbonaceous coating per unit specific surface area can be calculated from the specific surface area of the cathode material and the mass of the carbonaceous coating, as described later.
[0045] (Electrode active material)
[0046] The shape of the electrode active material particles is not particularly limited, but spherical, and especially true spherical, is preferred. By using spherical electrode active material particles, it has been found that the internal pores of the manufactured particulate matter (carbon-coated electrode active material) become more uniform, and it exhibits good electrolyte retention capacity. Furthermore, by forming particulate matter, the amount of solvent used in preparing the electrode forming paste using the positive electrode material for lithium-ion batteries of this embodiment can be reduced, and the coating of the current collector of the electrode forming paste becomes easier. In addition, the electrode forming paste can be prepared, for example, by mixing the positive electrode material for lithium-ion batteries of this embodiment, the binder resin (adhesive), and the solvent.
[0047] The electrode active material used in the positive electrode material for lithium-ion batteries in this embodiment is the electrode active material represented by the following general formula (1), which is preferred from the viewpoint of high discharge capacity, high energy density, safety and cycle stability.
[0048] Li a A x M y BO z (1)
[0049] (In the formula, A is selected from at least one of the groups consisting of Mn, Fe, Co and Ni; M is selected from at least one of the groups consisting of Na, K, Mg, Ca, Al, Ga, Ti, V, Cr, Cu, Zn, Y, Zr, Nb, Mo and rare earth elements; B is selected from at least one of the groups consisting of B, P, Si and S; 0≤a<4, 0<x<1.5, 0≤y<1, 0<z≤4.)
[0050] In the formula, A is selected from at least one of the group consisting of Mn, Fe, Co and Ni, wherein Mn and Fe are preferred, and Fe is more preferred.
[0051] M is selected from at least one of the following groups: Na, K, Mg, Ca, Al, Ga, Ti, V, Cr, Cu, Zn, Y, Zr, Nb, Mo, and rare earth elements, with Mg, Ca, Al, and Ti being preferred.
[0052] B is selected from at least one of the group consisting of B, P, Si and S, wherein P is preferred from the viewpoint of excellent safety and cycle characteristics.
[0053] a is 0 or more and less than 4, preferably 0.5 or more and less than 3, more preferably 0.5 or more and less than 2, and especially preferably 1. x is greater than 0 and less than 1.5, preferably 0.5 or more and less than 1, and preferably 1. y is 0 or more and less than 1, preferably 0 or more and less than 0.1. z is greater than 0 and less than 4, selected from the composition of B. For example, when B is phosphorus (P), z is preferably 4, and when B is boron (B), z is preferably 3.
[0054] The electrode active material represented by general formula (1) preferably has an olivine structure, more preferably it is the electrode active material represented by general formula (2) below, and in LiFePO4 and the LiFePO4, it is even more preferably Li(Fe) in which a portion of Fe is replaced by Mn. x1 Mn 1-x1 )PO4 (where 0 < x1 < 1).
[0055] Li a A x M y PO4 (2)
[0056] (In the formula, A, M, a, x, and y are as described above.)
[0057] The electrode active material represented by general formula (1) (Li a A x M y BO z It can be used to manufacture substances using conventional methods such as solid-phase, liquid-phase, and gas-phase methods.
[0058] Li a A x M y BO zFor example, it can be obtained by hydrothermal synthesis of a slurry mixture of Li source, A source, M source, B source and water, followed by washing the resulting precipitate with water. Furthermore, the same electrode active material can be obtained by hydrothermal synthesis to generate an electrode active material precursor, followed by calcination of the electrode active material precursor. A pressure-resistant, sealed container is preferably used in the hydrothermal synthesis.
[0059] Here, lithium salts such as lithium acetate (LiCH3COO), lithium chloride (LiCl), and lithium hydroxide (LiOH) can be used as Li sources, and it is preferred to use at least one selected from the group consisting of lithium acetate, lithium chloride, and lithium hydroxide.
[0060] Examples of sources A include chlorides, carboxylates, and sulfates selected from the group consisting of Mn, Fe, Co, and Ni. For example, when source A is Fe, divalent iron salts such as ferric chloride (II) (FeCl2), ferric acetate (II) (Fe(CH3COO)2), and ferric sulfate (II) (FeSO4) can be used as sources of Fe, with preference given to at least one salt selected from the group consisting of ferric chloride (II), ferric acetate (II), and ferric sulfate (II).
[0061] As a source of M, it can also use chlorides, carboxylates, sulfates, etc. of Na, K, Mg, Ca, Al, Ga, Ti, V, Cr, Cu, Zn, Y, Zr, Nb, Mo and rare earth elements.
[0062] Examples of B sources include compounds selected from the group consisting of B, P, Si, and S. For example, when the B source is P, examples of phosphoric acid compounds include phosphoric acid (H3PO4), ammonium dihydrogen phosphate (NH4H2PO4), and diammonium hydrogen phosphate ((NH4)2HPO4), with at least one selected from the group consisting of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate being preferred.
[0063] The molar ratio of Li, A, M and B sources (Li:A:M:B) can be appropriately selected to obtain the desired electrode active material without generating impurities.
[0064] The crystallite size of the electrode active material is preferably 30 nm or more and 250 nm or less, more preferably 35 nm or more and 250 nm or less, and even more preferably 40 nm or more and 200 nm or less. If the crystallite size is 30 nm or more, the amount of carbon required to fully coat the surface of the electrode active material with a carbonaceous film can be suppressed, and the amount of binder can also be suppressed. Therefore, the mass of the electrode active material in the electrode can be increased, and the battery capacity can be improved. Similarly, film peeling caused by insufficient adhesion is less likely to occur. On the other hand, if the crystallite size is 250 nm or less, the internal resistance of the electrode active material can be suppressed, and the discharge capacity at high charge / discharge rates can be improved when the battery is formed.
[0065] Furthermore, the microcrystal size can be determined using an X-ray diffraction apparatus (e.g., RINT2000, manufactured by RIGAKU), and calculated using the half-amplitude of the diffraction peaks on the (020) plane of the obtained powder X-ray diffraction pattern and the diffraction angle (2θ) by the Scherrer formula.
[0066] (Carbon coating)
[0067] A carbonaceous coating consisting of primary particles of an electrode active material and secondary particles that are aggregates of the primary particles can be obtained by carbonizing the organic matter that forms the raw material for the carbonaceous coating.
[0068] As organic compounds, examples include ionic organic compounds and nonionic organic compounds.
[0069] [Ionic organic compounds]
[0070] Examples of ionic organic compounds include, for example, sugars, polyacrylic acid, polystyrene sulfonic acid, polycarboxylic acid polymers, alkylbenzene sulfonates, alkyl sulfates, salts of carboxylic acid-modified polyvinyl alcohol, salts of sulfonic acid-modified polyvinyl alcohol, polycarboxylate salts, polyacrylates, polymethacrylates, and ionic surfactants.
[0071] [Nonionic organic compounds]
[0072] As nonionic organic compounds, polyvinyl alcohol (PVA), polyvinylpyrrolidone, polyacrylamide, polyvinyl acetate, polyether, diol, triol, nonionic surfactant, etc. are preferred.
[0073] These organic compounds can be used in single-component or mixed in combination with two or more.
[0074] The organic matter and the electrode active material particles are easy to mix. In order to obtain a uniform carbon coating, it is preferable that the organic matter used is solvent-soluble, and water-soluble is more preferable in terms of ease of operation, safety and price.
[0075] From the viewpoint of improving the output characteristics of lithium-ion batteries at low temperatures, it is preferable that the main component of the carbon coating is hard carbon. Here, "main component" means that the mass of hard carbon in the carbon coating is more than 50% by mass, preferably 70% by mass or more, more preferably 90% by mass or more, and even more preferably 97% by mass or more.
[0076] Hard carbon, also known as non-graphitizable carbon, is carbon that is difficult to develop a graphite crystal structure even when heated at high temperatures, and it has a porous structure.
[0077] From the viewpoint that it is easy to make the main component of carbon coating into hard carbon, the organic material is preferably a non-ionic organic material, and more preferably includes one or more of the group consisting of polyvinyl alcohol (PVA), polyvinylpyrrolidone and polyacrylamide, and even more preferably includes polyvinyl alcohol (PVA).
[0078] Furthermore, the method for producing hard carbon from the main component of the carbon coating will be explained in the manufacturing method of the positive electrode material for lithium-ion batteries, which will be described later.
[0079] The average particle size of the primary particles of the electrode active material coated with a carbonaceous film (carbonaceous coated electrode active material) is preferably 30 nm or more and 250 nm or less, more preferably 50 nm or more and 200 nm or less, even more preferably 50 nm or more and 150 nm or less, and even more preferably 60 nm or more and 100 nm or less. If the average particle size is 30 nm or more, the amount of binder required for electrode fabrication can be reduced, the mass of the electrode active material in the electrode can be increased, and the battery capacity can be improved. Furthermore, film peeling caused by insufficient adhesion can be suppressed. On the other hand, if the average particle size is 250 nm or less, sufficient high-speed charge-discharge performance can be obtained.
[0080] Here, the average particle size of primary particles refers to the number-average particle size. The average particle size of primary particles can be determined by averaging the particle sizes of more than 200 particles observed and measured by scanning electron microscopy (SEM).
[0081] The average particle size of the secondary particles in the carbonaceous coated electrode active material is preferably 0.5 μm or more and 200 μm or less, more preferably 1 μm or more and 150 μm or less, and even more preferably 3 μm or more and 100 μm or less. If the average particle size of the secondary particles is 0.5 μm or more, when preparing a positive electrode material paste for lithium-ion batteries by mixing positive electrode materials, conductive additives, binder resins (binders), and solvents, the need for large amounts of conductive additives and binders can be suppressed. This can improve the battery capacity of the lithium-ion battery. On the other hand, if the particle size is 200 μm or less, the discharge capacity of the lithium-ion battery during high-speed charging and discharging can be improved.
[0082] Here, the average particle size of secondary particles refers to the volume average particle size. The average particle size of the secondary particles can be measured using a laser diffraction scattering particle size distribution measuring device or the like.
[0083] The thickness (average value) of the carbonaceous coating covering the electrode active material particles is preferably 0.5 nm or more and 10 nm or less, more preferably 0.8 nm or more and 8 nm or less, even more preferably 0.8 nm or more and 8 nm or less, and even more preferably 0.8 nm or more and 5 nm or less. If the thickness of the carbonaceous coating is 0.5 nm or more, the sum of electron migration resistance in the carbonaceous coating can be suppressed from increasing. This suppresses the increase in the internal resistance of the lithium-ion battery and prevents voltage drop at high charging and discharging rates. On the other hand, if the thickness is 10 nm or less, the formation of steric hindrance hindering the diffusion of lithium ions in the carbonaceous coating can be suppressed, thereby reducing the lithium-ion migration resistance. As a result, the increase in the internal resistance of the battery can be suppressed, and voltage drop at high charging and discharging rates can be prevented.
[0084] In addition, the thickness of the carbon coating can be determined by taking pictures of the carbon-coated electrode active material using a transmission electron microscope (TEM) or a scanning electron microscope (SEM), measuring the thickness of the carbon coating at 100 points from the obtained cross-sectional image, and then calculating the thickness from the average value.
[0085] The coating rate of the carbonaceous film relative to the electrode active material particles is preferably 60% or more, more preferably 80% or more. With a coating rate of 60% or more, the coating effect of the carbonaceous film can be sufficiently obtained.
[0086] In addition, the coverage rate of the carbon coating can be determined by observing the carbon-coated electrode active material using a transmission electron microscope (TEM) or an energy dispersive X-ray microanalyzer (EDX), calculating the proportion of the portion covering the surface of the electrode active material, and then obtaining the coverage rate from the average value.
[0087] The density of the carbon coating is preferably 0.2 g / cm³. 3 Above and 2g / cm 3 The following is more preferably 0.5 g / cm³. 3 Above and 1.5g / cm 3 Below. The density of carbon coating refers to the mass per unit volume of the carbon coating.
[0088] If the density of the carbon coating is 0.2 g / cm³ 3 Therefore, the carbon coating exhibits sufficient electronic conductivity. On the other hand, if it is 2 g / cm³... 3 Since the amount of graphite crystals with a layered structure in the carbonaceous coating is small, no steric hindrance caused by the graphite crystals occurs during lithium-ion diffusion within the carbonaceous coating. Therefore, the lithium-ion migration resistance does not increase. Consequently, the internal resistance of the lithium-ion battery does not rise, and there is no voltage drop at high charging and discharging rates.
[0089] In this embodiment, the carbon content (the carbon content contained in the positive electrode material for lithium-ion batteries) of the positive electrode material is considered to be the same as the mass of the carbon coating in the positive electrode material, preferably 0.5% by mass or more and 3.5% by mass or less, more preferably 0.8% by mass or more and 2.5% by mass or less, and even more preferably 0.8% by mass or more and 2.2% by mass or less. If the carbon content is 0.5% by mass or more, the electronic conductivity can be sufficiently improved. On the other hand, if the carbon content is 3.5% by mass or less, the electrode density can be improved.
[0090] In addition, the carbon content can be measured using a carbon analyzer (e.g., HORIBA, Ltd., carbon and sulfur analysis device: EMIA-220V).
[0091] In this embodiment, the specific surface area of the positive electrode material for lithium-ion batteries is preferably 4m². 2 / g or more and 40m 2 / g or less, preferably 8m 2 / g or more and 28m 2 / g or less, more preferably 10m 2 / g or more and 25m2 / g or less, more preferably 11m 2 / g or more and 22m 2 / g or less.
[0092] If the specific surface area is 4m² 2 If the value is above / g, it can exhibit sufficient high-speed charging and discharging performance. On the other hand, if it is 40m 2 With a content of less than / g, electrodes can be formed without containing a large amount of binder and conductive additives, thus suppressing the reduction of battery capacity.
[0093] In addition, the specific surface area can be measured using a gas adsorption measuring device (e.g., manufactured by MOUNTECH Co., Ltd., trade name: HM model-1208) by nitrogen (N2) adsorption.
[0094] <Manufacturing Method of Cathode Material for Lithium-ion Batteries>
[0095] The method for manufacturing a positive electrode material for lithium-ion batteries according to this embodiment includes: a first step, using a spray dryer to dry and granulate a slurry containing an organic material that serves as a carbon source, one or more electrode active materials and electrode active material precursors, and a solvent; and a second step, subjecting the granulated material obtained in the first step to heat treatment (calcination) for 0.5 to 24 hours in a superheated steam atmosphere.
[0096] Using organic matter as a carbon source, a slurry mixed with one or more electrode active materials and precursors and a solvent is dried, granulated, and then heat-treated (calcined) for 0.5 to 24 hours in a superheated steam atmosphere. The resulting cathode material easily satisfies the requirements of Equation (1) by ensuring that the powder resistance and the mass of the carbon coating per unit specific surface area are within the range described. Furthermore, this manufacturing method easily forms a carbon coating whose main component is hard carbon.
[0097] (First process)
[0098] This process involves using a spray dryer to dry and granulate a slurry containing an organic mixture serving as a carbon source, one or more electrode active materials and precursors selected from electrode active materials, and a solvent.
[0099] First, an organic compound and one or more selected from electrode active substances and electrode active substance precursors are dissolved or dispersed in a solvent to prepare a mixture.
[0100] There are no particular limitations on the method of coating an organic substance onto a material selected from electrode active materials and electrode active material precursors, and dissolving or dispersing it in a solvent. For example, a dispersion device such as a planetary ball mill, a vibratory ball mill, a bead mill, a paint mixer, or a grinder can be used.
[0101] From the viewpoint of improving the output characteristics of lithium-ion batteries at low temperatures, it is preferable to use a bead mill to mix organic matter, one or more of the electrode active material and electrode active material precursors, and a solvent; more preferably, it is preferable to use a bead mill that uses zirconia beads with a diameter of 0.05 to 0.5 mm.
[0102] Regarding organic matter, electrode active material and electrode active material precursor, as described above, from the viewpoint that the main component of the carbonaceous coating is hard carbon, the organic matter is preferably a nonionic organic matter, more preferably including one or more selected from the group consisting of polyvinyl alcohol (PVA), polyvinylpyrrolidone and polyacrylamide, and even more preferably including polyvinyl alcohol (PVA).
[0103] Examples of solvents include: water; alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol: IPA), butanol, pentanol, hexanol, octanol, and diacetone alcohol; esters such as ethyl acetate, butyl acetate, ethyl lactate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and γ-butyrolactone; ethers such as diethyl ether, ethylene glycol monomethyl ether (methyl cellosolve), ethylene glycol monoethyl ether (ethyl cellosolve), ethylene glycol monobutyl ether (butyl cellosolve), diethylene glycol monomethyl ether, and diethylene glycol monoethyl ether; ketones such as acetone, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), acetylacetone, and cyclohexanone; amides such as dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; and diols such as ethylene glycol, diethylene glycol, and propylene glycol. One or more of these solvents may be used. Water is the preferred solvent among these solvents.
[0104] Additionally, dispersants can be added as needed.
[0105] The ratio of organic matter to one or more selected electrode active materials and electrode active material precursors is preferably 0.5 parts by mass and 10 parts by mass and less, based on the mass of carbon obtained from the organic matter, relative to 100 parts by mass of active material obtained from one or more selected electrode active materials and electrode active material precursors. The actual mixing amount varies depending on the amount of carbonization based on heating carbonization (type of carbon source, carbonization conditions, etc.), and is usually around 1 to 8 parts by mass.
[0106] Furthermore, when dissolving or dispersing the organic compound and one or more selected from electrode active materials and electrode active material precursors in a solvent, it is preferable to add the organic compound and stir after dispersing one or more selected from electrode active materials and electrode active material precursors in the solvent.
[0107] Next, the obtained slurry is dried and granulated using a spray dryer to obtain granules.
[0108] (Second process)
[0109] This process involves heat-treating (calcining) the granules obtained in the first process under a superheated steam atmosphere for 0.5 to 24 hours.
[0110] Hard carbon can be easily produced from the main component of the carbonaceous coating by heat-treating (calcining) the granules in a superheated steam atmosphere for 0.5 to 24 hours. Hard carbon is not easily formed in inert atmospheres such as nitrogen (N2) or argon (Ar) during heating.
[0111] Furthermore, since the heat treatment time is 0.5 to 24 hours, the granules are not calcined excessively or insufficiently, and hard carbon is easily generated from the organic matter.
[0112] The heat treatment time is preferably 0.8 to 10 hours, more preferably 1 to 6 hours, and even more preferably 1 to 3 hours.
[0113] The temperature of the heat treatment is usually above 600°C and below 1000°C, preferably above 650°C and below 900°C, more preferably above 700°C and below 850°C, and even more preferably above 700°C and below 800°C.
[0114] Because the heat treatment temperature is above 600℃, it is easy to fully carbonize organic matter, which can improve electronic conductivity. Because it is below 1000℃, it is not easy to decompose the electrode active material particles, and it is easy to inhibit particle growth.
[0115] According to the manufacturing method of this embodiment, by using organic matter as a precursor for carbonaceous coating, the coating properties are improved. This suppresses the proximity of electrode active material particles to each other, thus enabling the easy production of fine and highly reactive lithium-ion battery cathode materials that are coated with carbonaceous material that does not contain excessive carbon and has higher electronic conductivity. Furthermore, it allows for the fabrication of granules with an appropriate pore size distribution that exhibit excellent electrolyte permeability and retention. The resulting lithium-ion battery cathode material improves electrode density and enables the formation of lithium-ion batteries with excellent output characteristics at low temperatures.
[0116] Furthermore, the positive electrode material for lithium-ion batteries in this embodiment has a large specific surface area and a small particle size, thus exhibiting good reactivity, especially in low-temperature reactions where charge migration on the surface of electrode active material particles and ion diffusion within the electrode active material particles is reduced.
[0117] The manufacturing method described in this embodiment is applicable regardless of the type of electrode active material, but it is particularly effective as a method for manufacturing a low-cost, low-environmental-impact, low-electronic-conductivity positive electrode material for olivine-type phosphate-based lithium-ion batteries.
[0118] <Positive electrode for lithium-ion batteries>
[0119] The positive electrode for the lithium-ion battery in this embodiment is made using the positive electrode material for the lithium-ion battery in this embodiment.
[0120] When manufacturing the positive electrode for a lithium-ion battery according to this embodiment, the above-mentioned positive electrode material for lithium-ion batteries, a binder including a binder resin, and a solvent are mixed to prepare an electrode forming coating or an electrode forming paste. Conductive additives such as carbon black, acetylene black, graphite, Ketjen black, natural graphite, and artificial graphite can be added as needed.
[0121] As a binder or adhesive resin, polytetrafluoroethylene (PTFE) resin, polyvinylidene fluoride (PVdF) resin, fluororubber, etc. are preferred.
[0122] There is no particular limitation on the mixing ratio of positive electrode material and binder resin for lithium-ion batteries. For example, relative to 100 parts by weight of positive electrode material for lithium-ion batteries, the binder resin is set to 1 part by weight or more and 30 parts by weight or less, preferably 3 parts by weight or more and 20 parts by weight or less.
[0123] The solvent used in coatings or pastes for electrode forming can be appropriately selected based on the properties of the adhesive resin.
[0124] Examples include: water; alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol: IPA), butanol, pentanol, hexanol, octanol, and diacetone alcohol; esters such as ethyl acetate, butyl acetate, ethyl lactate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and γ-butyrolactone; ethers such as diethyl ether, ethylene glycol monomethyl ether (methyl cellosolve), ethylene glycol monoethyl ether (ethyl cellosolve), ethylene glycol monobutyl ether (butyl cellosolve), diethylene glycol monomethyl ether, and diethylene glycol monoethyl ether; ketones such as acetone, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), acetylacetone, and cyclohexanone; amides such as dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone (NMP); and diols such as ethylene glycol, diethylene glycol, and propylene glycol. Only one type of these can be used, or two or more can be mixed.
[0125] Next, an electrode forming coating or electrode forming paste is applied to one side of the metal foil, and then dried to obtain a metal foil with a coating film formed on one side of the mixture of the above-mentioned positive electrode material for lithium-ion batteries and adhesive resin.
[0126] Next, the coating is pressed under pressure and dried to create a current collector (electrode) with a positive electrode material layer for lithium-ion batteries on one side of the metal foil.
[0127] In this way, electrodes with excellent output characteristics at low temperatures can be produced.
[0128] <Lithium-ion batteries>
[0129] The lithium-ion battery of this embodiment includes the positive electrode for lithium-ion batteries of this embodiment. Therefore, the lithium-ion battery of this embodiment can improve its output characteristics at low temperatures.
[0130] In the lithium-ion battery of this embodiment, there are no particular limitations on the negative electrode, electrolyte, separator, etc. For example, metallic Li, carbon materials, Li alloys, and Li4Ti5O can be used as the negative electrode. 12 Other negative electrode materials. Furthermore, solid electrolytes can be used instead of electrolytes and membranes.
[0131] Example
[0132] The present invention will now be specifically described with reference to embodiments and comparative examples. However, the present invention is not limited to the methods described in the embodiments.
[0133] <Manufacturing Example 1: Manufacturing of Electrode Active Material (LiFePO4)>
[0134] The synthesis of LiFePO4 was carried out via hydrothermal synthesis as follows.
[0135] LiOH was used as the Li source, NH4H2PO4 as the P source, and FeSO4·7H2O as the Fe source. They were mixed in pure water in a mass ratio of Li:Fe:P = 3:1:1 to prepare a homogeneous slurry of 200 mL.
[0136] Next, the mixture was placed in a 500 mL pressure-resistant sealed container and subjected to hydrothermal synthesis at 170 °C for 12 hours. After the reaction, it was cooled to room temperature (25 °C) to obtain a precipitated cake-like product. The precipitate was thoroughly washed several times with distilled water, maintaining a moisture content of 30% to prevent drying, thus forming a cake-like substance. A small amount of this cake-like substance was collected and analyzed by X-ray diffraction using a RINT2000 (manufactured by RIGAKU) device. The powder obtained after vacuum drying at 70 °C for 2 hours was confirmed to contain a single-phase LiFePO4.
[0137] [Example 1]
[0138] 20g of LiFePO4 (electrode active material) obtained in the manufacturing example and 0.73g of polyvinyl alcohol as a carbon source were mixed in water to make a total of 100g. 150g of zirconia beads were bead-milled together to obtain a slurry (mixture) with a dispersed particle size (d50) of 100nm.
[0139] Then, the powder was dried and granulated using a spray dryer at a drying outlet temperature of 60°C. The granulated powder was then heat-treated for 1 hour in a rotary kiln with a superheated steam atmosphere in a tubular furnace to obtain a cathode material composed of carbon-coated electrode active material.
[0140] [Example 2]
[0141] The amount of polyvinyl alcohol was set to 0.80 g. Otherwise, a positive electrode material composed of carbonaceous coated electrode active material was obtained in the same manner as in Example 1.
[0142] [Example 3]
[0143] The amount of polyvinyl alcohol was set to 0.87g. Otherwise, a positive electrode material composed of carbonaceous coated electrode active material was obtained in the same manner as in Example 1.
[0144] [Example 4]
[0145] The amount of polyvinyl alcohol was set to 0.94 g. Otherwise, a positive electrode material composed of carbonaceous coated electrode active material was obtained in the same manner as in Example 1.
[0146] [Example 5]
[0147] The amount of polyvinyl alcohol was set to 0.65g. Otherwise, a positive electrode material composed of carbonaceous coated electrode active material was obtained in the same manner as in Example 1.
[0148] [Example 6]
[0149] Without bead milling using zirconia beads, a positive electrode material composed of carbonaceous coated electrode active material was obtained in the same manner as in Example 1.
[0150] [Example 7]
[0151] Without bead milling using zirconia beads, a positive electrode material composed of carbonaceous coated electrode active material was obtained in the same manner as in Example 5.
[0152] [Comparative Example 1]
[0153] The heat treatment atmosphere was set to nitrogen, and otherwise, a positive electrode material composed of carbonaceous coated electrode active material was obtained in the same manner as in Example 1.
[0154] [Comparative Example 2]
[0155] The heat treatment atmosphere was set to nitrogen, and otherwise, a positive electrode material composed of carbonaceous coated electrode active material was obtained in the same manner as in Example 2.
[0156] [Comparative Example 3]
[0157] The heat treatment atmosphere was set to nitrogen, and otherwise, a positive electrode material composed of carbonaceous coated electrode active material was obtained in the same manner as in Example 3.
[0158] [Comparative Example 4]
[0159] The amount of polyvinyl alcohol was set to 0.58g. Otherwise, a positive electrode material composed of carbonaceous coated electrode active material was obtained in the same manner as in Example 1.
[0160] [Comparative Example 5]
[0161] The amount of polyvinyl alcohol was set to 1.5g. Otherwise, a positive electrode material composed of carbonaceous coated electrode active material was obtained in the same manner as in Example 1.
[0162] <Characteristics of cathode materials>
[0163] 1. Determination of powder resistivity
[0164] The positive electrode material was placed into a mold and pressurized at 50 MPa to form a molded body. The powder resistivity of the molded body was measured at 25°C using a low resistivity meter (manufactured by Mitsubishi Chemical Analytech Co., Ltd., trade name: Loresta-GP) and the four-terminal method.
[0165] 2. Determination of specific surface area
[0166] The specific surface area of the cathode material was determined using a specific surface area meter (manufactured by MOUNTECH Co., Ltd., trade name: HM model-1208) and the BET method based on nitrogen (N2) adsorption.
[0167] 3. Determination of carbon content
[0168] The mass of the carbonaceous coating was determined using a carbon sulfur analyzer (manufactured by HORIBA, Ltd., trade name: EMIA-220V) and expressed as a percentage of the cathode material.
[0169] 4. Thickness of carbon coating
[0170] The cathode material was imaged using a transmission electron microscope (TEM; manufactured by Hitachi High-Tech Corporation, model: HF2000) at an accelerating voltage of 200kV and a magnification of 200,000x. In the obtained cross-sectional images, a field of view of 180nm × 180nm was observed at 10 arbitrary points, and the thickness of the carbon coating at these 100 points was measured. The average value of these measurements was taken as the thickness of the carbon coating.
[0171] 5. Mass of carbonaceous coating per specific surface area
[0172] From the results of "2. Determination of specific surface area" and "3. Determination of carbon content" above, calculate the carbon content (g / g) / specific surface area (m²). 2 / g)×1000=Carbon content per specific surface area (mg / m²) 2 ).
[0173] <The Manufacturing of Lithium-ion Batteries>
[0174] (The production of the positive electrode)
[0175] The positive electrode material obtained in the examples and comparative examples, acetylene black (AB) as a conductive additive, and polyvinylidene fluoride (PVdF) resin as a binder were mixed in N-methylpyrrolidone (NMP) at a mass ratio of positive electrode material:AB:PVdF = 90:5:5 to prepare a positive electrode material paste. The obtained paste was coated onto an aluminum foil with a thickness of 30 μm, dried, and then pressed by a roller press with a pressure interval of 30 μm to form an electrode plate.
[0176] (Battery manufacturing)
[0177] The obtained electrode plate is punched into pieces with an area of 2 cm² using a circular punching machine. 2 The circular shape was dried at 60°C for 15 hours using a vacuum dryer, and then a coin cell with lithium as the negative electrode was produced in a glove box.
[0178] <Evaluation of Lithium-ion Batteries>
[0179] (Evaluation of low-temperature properties)
[0180] The obtained coin cells were charged at 25°C at a rate of 0.1C, and then the discharge capacity at -30°C and 1C was measured, thus obtaining the low-temperature discharge capacity. The results are shown in Table 1 and... Figure 1 .
[0181] Figure 1 This is a graph showing the powder resistivity relative to the carbon content per unit specific surface area in the cathode materials of Examples 1 to 7, Comparative Examples 1 to 5, and examples with changes in carbon content, calcination atmosphere, and other manufacturing methods. Figure 1 In formula (1), the powder resistivity Y is defined as being in the range of 500 Ω·cm or higher and 50000 Ω·cm or lower, and the mass X of the carbonaceous coating per unit specific surface area is defined as being 0.7 mg / m³. 2 Above and 1.1 mg / m 2 The following range is represented by solid lines, which will be derived from equation (1) as "Y = 4.91 × 10 6 ×e -9.021X The straight line is represented by a dashed line.
[0182] [Table 1]
[0183]
[0184] As shown in Table 1, although the powder resistivity is between 500 Ω·cm and 50,000 Ω·cm, the mass of the carbonaceous coating per unit specific surface area is less than 0.7 mg / m³. 2 Comparative Example 1; Comparative Example 2, although the powder resistance and the mass of the carbon coating per unit specific surface area are within the scope of the present invention, do not satisfy Equation (1); Comparative Example 4, although the magnitude relationship of Equation (1) is satisfied, the powder resistance and the mass of the carbon coating per unit specific surface area do not satisfy the scope of the present invention; and Comparative Examples 3 and 5, which are not within the scope of the present invention and do not satisfy Equation (1), all have a capacity of 65 mAh / g or less at -30°C, and their output characteristics at low temperatures are not excellent. In contrast, the lithium-ion batteries using the cathode materials of the embodiments all have a capacity of 80 mAh / g or more at -30°C, and their output characteristics at low temperatures are excellent.
Claims
1. A positive electrode material for lithium-ion batteries, comprising primary particles or aggregates thereof coated with a carbonaceous film, having a powder resistivity of 500 Ω•cm or higher and 50000 Ω•cm or lower, and a carbonaceous film mass of 0.7 mg / m³ per unit specific surface area. 2 Above and 1.1 mg / m 2 The following, and satisfying the following equation (1): Y≥4.91×10 6 ×e -9.021X (1) Y: The resistance of the powder, in Ω•cm X: The mass of the carbonaceous coating per unit specific surface area, expressed in mg / m³. 2 ; in, The hard carbon in the carbon coating is 70% by mass or more.
2. The positive electrode material for lithium-ion batteries according to claim 1, wherein, The thickness of the carbon coating is greater than 0.5 nm and less than 10 nm.
3. A positive electrode for a lithium-ion battery, which uses the positive electrode material for a lithium-ion battery as described in claim 1 or 2.
4. A lithium-ion battery comprising the positive electrode for a lithium-ion battery as described in claim 3.
Citation Information
Patent Citations
Speedy advance and retreat device of interlocking part of threaded shaft
JP1982043011A
Semiconductor memory device
JP1987088338A